PENGARUH PEMANFAATAN TEKNOLOGI, PARTISIPASI PEMAKAI, MANAJEMEN PUNCAK DAN KEMAMPUAN PEMAKAI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Pardani, Kadek Kusuma; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi, 2017)
Computer-based accounting information system is essential applied in cooperatives to produce a form of financial statements information that is relevant and reliable. This study aims to demonstrate empirically the effect of the use of information technology, user participation, top management support and engineering capabilities users of accounting information systems at the effectiveness of accounting information systems. Sampling technique used is the census sampling technique (saturated sample) and get a sample of 100 samples. Questionnaires were returned and deserves to be treated as many as 100 questionnaires. Data analysis technique used is the technique of linear regression analysis showed that the variables berganda.Hasil use of information technology, user participation, top management support, the ability of users of accounting information systems engineering positive influence on the effectiveness of the system of accounting informmasi.
Keywords: Information Technology Utilization, User Participation, Top Management Support, Effectiveness SIA